ALK Fusions in a Wide Variety of Tumor Types Respond to Anti‐ALK Targeted Therapy. (4th December 2017) - Ross, Jeffrey S.; Ali, Siraj M.; Fasan, Omotayo; Block, Jared; Pal, Sumanta; Elvin, Julia A.; Schrock, Alexa B.; Suh, James; Nozad, Sahar; Kim, Sungeun; Jeong Lee, Hwa; Sheehan, Christine E.; et al.
Abstract: Background: Genomic fusions of the anaplastic lymphoma kinase gene ( ALK ) are a well‐established therapy target in non‐small cell lung cancer (NSCLC). From a survey of 114, 200 clinical cases, we determined the prevalence of ALK rearrangements (r ALK ) in non‐NSCLC tumors and report their responsiveness to therapies targeting ALK. Materials and Methods: Comprehensive genomic profiling of 114, 200 relapsed and metastatic malignancies, including both solid tumors and hematolymphoid cancers, was performed using a hybrid‐capture, adaptor ligation‐based next‐generation sequencing assay. Results: Of 114, 200 clinical samples, 21, 522 (18.8%) were NSCLC and 92, 678 (81.2%) were other tumor types. Of the 876 (0.8%) cases with ALK fusions (f ALK ) or rALK, 675 (77.1%) were NSCLC and 201 (22.9%) were other tumor types. ALK fusions were significantly more frequent in NSCLC (3.1%) than non‐NSCLC (0.2%; p  < .0001). Patients with non‐NSCLC tumors harboring f ALK were significantly younger ( p  < .0001) and more often female ( p  < .0001) than patients with f ALK ‐positive NSCLC. EML4 was more often the fusion partner in NSCLC (83.5%) versus non‐NSCLC tumors (30.9%; p  < .0001). Conclusion: ALK rearrangements can be identified in a wide variety of epithelial and mesenchymal malignancies beyond NSCLC. Anti‐ALK therapies can be effective in non‐NSCLC tumors driven by f ALK, and further study of therapies targeting ALK in clinical trials involving a wider variety of cancer types appears warranted. Abstract : This article reports a series of 114, 200 consecutive clinical cases with comprehensive genomic profiles available to identify ALK fusions that could facilitate the use of precision medicine in both non‐small cell lung cancer (NSCLC) and non‐NSCLC malignancies.